Extended criteria donors in liver transplantation Part I: reviewing the impact of determining factors. (2nd July 2016) - Nemes, Balázs; Gámán, György; Polak, Wojciech G.; Gelley, Fanni; Hara, Takanobu; Ono, Shinichiro; Baimakhanov, Zhassulan; Piros, Laszlo; Eguchi, Susumu
ABSTRACT: The definition and factors of extended criteria donors have already been set; however, details of the various opinions still differ in many respects. In this review, we summarize the impact of these factors and their clinical relevance. Elderly livers must not be allocated for hepatitis C virus (HCV) positives, or patients with acute liver failure. In cases of markedly increased serum transaminases, donor hemodynamics is an essential consideration. A prolonged hypotension of the donor does not always lead to an increase in post-transplantation graft loss if post-OLT care is proper. Hypernatremia of less than 160 mEq/L is not an absolute contraindication to accept a liver graft per se. The presence of steatosis is an independent and determinant risk factor for the outcome. The gold standard of the diagnosis is the biopsy. This is recommended in all doubtful cases. The use of HCV+ grafts for HCV+ recipients is comparable in outcome. The leading risk factor for HCV recurrence is the actual RNA positivity of the donor. The presence of a proper anti-HBs level seems to protect from de novo HBV infection. A favourable outcome can be expected if a donation after cardiac death liver is transplanted in a favourable condition, meaning, a warm ischemia time < 30 minutes, cold ischemia time < 8–10 hours, and donor age 50–60 years. The pathway of organ quality assessment is to obtain the most relevant information (e.g. biopsy), consider the co-existing donor risk factors and the reserve capacity of the recipient, and avoid further technical issues.